Efektivitas Kartu Kata Canva untuk Meningkatkan Keterampilan Membaca dan Menulis Permulaan Kelas 1 Sekolah Dasar - Salsabella Asih Wulandari; Deri Anggraini (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to ascertain the extent to which interactive word card media based on the Canva software may improve the beginning reading and writing skills of first-grade children at SD Negeri 1 Kadipiro. This study uses an uneven control group design and experimental methodologies to take a quantitative approach. Two groups of 28 students each made up the research subjects: the experimental group used word cards created with the Canva program, and the control group used word cards with concrete pictures. Among the tools used are observation sheets to gauge media use and preliminary tests of reading and writing abilities.  Data analysis shows that students in the experimental class scored much higher on average for reading and writing skills than students in the control group.  The Independent Sample T-Test hypothesis test yielded a significance result of 0.000, which is less than 0.05. This suggests that two groups differ significantly from one another. According to this study, children' early basic reading abilities are more effectively developed when interactive word card media based on the Canva software is used. Therefore, at the primary school level, digital medium can enhance the process of learning fundamental reading and writing in a creative and useful way.